Association of Female Genital Schistosomiasis With the Cervicovaginal Microbiota and Sexually Transmitted Infections in Zambian Women. (22nd August 2021) - Sturt, Amy S; Webb, Emily L; Himschoot, Lisa; Phiri, Comfort R; Mapani, Joyce; Mudenda, Maina; Kjetland, Eyrun F; Mweene, Tobias; Levecke, Bruno; van Dam, Govert J; Corstjens, Paul L A M; Ayles, Helen; et al.
Abstract: Background: The cervicovaginal microbiota, including sexually transmitted infections (STIs), have not been well described in female genital schistosomiasis (FGS). Methods: Women (aged 18–31, sexually active, nonpregnant) were invited to participate at the final follow-up of the HPTN 071 (PopART) Population Cohort in January–August 2018. We measured key species of the cervicovaginal microbiota ( Lactobacillus crispatus, L. iners, Gardnerella vaginalis, Atopobium vaginae, and Candida ) and STIs ( Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and Mycoplasma genitalium ) using quantitative PCR (qPCR). We evaluated associations of the microbiota and STI presence and concentration with FGS (qPCR-detected Schistosoma DNA in any of 3 genital specimens). Results: The presence and concentration of key cervicovaginal species did not differ between participants with (n = 30) or without FGS (n = 158). A higher proportion of participants with FGS had T. vaginalis compared with FGS-negative women ( P = .08), with further analysis showing that T. vaginalis was more prevalent among women with ≥2 Schistosoma qPCR-positive genital specimens (50.0%, 8/16) than among FGS-negative women (21.5%, 34/158; P = .01). Conclusions: We found weak evidence of an association between the presence of T. vaginalis and FGS, with a stronger association in women with a higher-burden FGS infection. Additional research is needed on potential between-parasite interactions, especially regarding HIV-1 vulnerability.